In Vitro Probiotic Evaluation of Yeasts from Coconut and Raffia Juices - Emenike O. Irokanulo; Queen-Esther M. Yadung; Dolapo E. Orotayo; Charles O. Nwonuma; Oreoluwa S. Alonge (Техника и технология пищевых производств)
Eukaryotic probiotics currently attract a lot of scientific attention, with Saccharomyces cerevisiae and Saccharomyces boulardii being the most widely investigated probiotic yeasts. The range of yeast species with probiotic potential needs to be broadened. In this respect, juice-providing plants may diversify eukaryotic probiotic sources for organism preference. This study tested the probiotic potential of Pichia kudriavzevii and Kluyveromyces marxianus isolated from coconut juice and Schizosaccharomyces pombe and Wickherhamomyces anomalus isolated from raffia palm juice in Nigeria. The in vitro tests used the optical density method to assay the tolerance to acid (pH 2, 3, 5), alkaline (pH 7.5, 8.0), gastric juice (30%), bile (1, 2, and 3%), and osmotic pressure (5, 10, 15, 20, 25, and 30% glucose solution). All four yeasts survived in the test environments, exhibiting varying degrees of probiotic potential. After 96 h in simulated gastric juice, S. pombe outperformed K. marxianus and W. anomalus by 13 and 97.7% (p < 0.05), respectively. W. anomalus appeared to be the least viable in 30% gastric juice. After 96 h in the acid media, all yeasts performed better at pH 3.0 than at pH 2.0, with roughly 89% (1.695/0.185 mean absorbance values) greater growth in pH 3.0 than in pH 2.0. The alkaline media had a better effect on the growth rate. P. kudriavzevii fared best at pH 2.0 and 3.0 for up to 96 h. All yeasts maintained viability in 1, 2, and 3% bile solutions, although the growth rate did not improve significantly in any of the assay periods. Only minimal growth increase was registered in increased bile concentrations. All samples demonstrated sustained viability in 5–30% glucose between 24 and 48 h of incubation. After 48 h of incubation, the yeast concentrations began to fall as the glucose concentration rose from 5 to 30%. P. kudriavzevii was the least affected after 96 h (41.8%) and demonstrated the best survival results by the four criteria tested in this study. If this species meets all other non-assayed parameters which qualify a microorganism as a probiotic, P. kudriavzevii obtained from Nigerian coconut juice can be recommended as a potential source of commercial probiotics.